2023
DOI: 10.1111/acel.13932
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 exacerbates the senescence of hippocampal neurons and spatial cognitive impairment by downregulating acetyl‐CoA level

Shuixin Lv,
Yusi Zhang,
Yingbin Lin
et al.

Abstract: Although aging and apolipoprotein E (APOE) ε4 allele have been documented as two major risk factors for late‐onset Alzheimer's disease (LOAD), their interaction and potential underlying mechanisms remain unelucidated. Using humanized ApoE4‐ and ApoE3‐ target replacement mice, we found the accumulation of senescent neurons and the activation of mTOR and endosome‐lysosome‐autophagy (ELA) system in the hippocampus of aged ApoE4 mice. Further analyses revealed that ApoE4 aggravated the profile change of hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Cholesterol and lipid accumulation has been reported in cellular and mouse models of Aβ [63, 64], tau [65, 66] and APOE4 [39,[67][68][69]. A recent study identi ed more senescent neurons in the hippocampus of old ApoE4-TR mice than in ApoE3-TR mice owing to dysregulation of ATP and acetyl coenzyme A [14], which are substrates for cholesterol synthesis [70]. Cholesterol localization shifts to lysosomes, leading to the formation of microdomains enriched for the mTORC1 scaffolding complex, priming mTORC1 for activation, and increasing proin ammatory SASP [5,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol and lipid accumulation has been reported in cellular and mouse models of Aβ [63, 64], tau [65, 66] and APOE4 [39,[67][68][69]. A recent study identi ed more senescent neurons in the hippocampus of old ApoE4-TR mice than in ApoE3-TR mice owing to dysregulation of ATP and acetyl coenzyme A [14], which are substrates for cholesterol synthesis [70]. Cholesterol localization shifts to lysosomes, leading to the formation of microdomains enriched for the mTORC1 scaffolding complex, priming mTORC1 for activation, and increasing proin ammatory SASP [5,71].…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E4 allele (APOE4) is the strongest genetic risk factor for late-onset AD [12,13]. More senescent neurons were found in APOE4-target replacement (APOE4-TR) mice than in APOE3-TR mice [14]. Arguably, APOE4's major effects in the brain are mediated by its cholesterol-transporting capability [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we observed neurotoxicity associated with APOE4 -TR microglia compared to APOE3 -TR microglia, which aligns with a recent publication that demonstrates the exacerbation of neuronal senescence in APOE4 -TR mice. 82 This phenotype may be attributed, at least in part, to the larger size of microglial APOE4 particles, because previous studies have linked larger-sized apoE particles with neurotoxicity. 36 , 83 Additionally, we observed lower GPNMB/APOE ratio in APOE4 particles, compared to that in APOE3 particles, suggesting that GPNMB might not be the primary culprit for the neurotoxic effects of microglial APOE4 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Separate from microglia, ApoE4 was recently found to decrease acetyl-CoA levels in hippocampal neurons of elderly ApoE4 mice, resulting in cellular senescence (Lv et al, 2023). Supplying glycerol triacetate (GTA) to increase acetyl-CoA levels to ApoE4 elderly mice decreased cellular senescence in neurons and increased expression of proteins related to synaptic plasticity.…”
Section: Apolipoprotein-e4mentioning
confidence: 99%